2012
DOI: 10.1088/1367-2630/14/1/013041
|View full text |Cite
|
Sign up to set email alerts
|

Identification of clusters of investors from their real trading activity in a financial market

Abstract: We use statistically validated networks, a recently introduced method to validate links in a bipartite system, to identify clusters of investors trading in a financial market. Specifically, we investigate a special database allowing to track the trading activity of individual investors of the stock Nokia. We find that many statistically detected clusters of investors show a very high degree of synchronization in the time when they decide to trade and in the trading action taken. We investigate the composition … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 59 publications
3
75
0
Order By: Relevance
“…The decrease of mean degree can be interpreted in the following way: as γ increases, the interaction involving the same pair of agents is repeated and effectively a dimerisation takes place. Similar dimers and small clusters have been observed by Tumminello et al [27] for agents in stock market data. Crossover to a dimerised state occurs as γ is increased.…”
Section: Model Bsupporting
confidence: 87%
See 1 more Smart Citation
“…The decrease of mean degree can be interpreted in the following way: as γ increases, the interaction involving the same pair of agents is repeated and effectively a dimerisation takes place. Similar dimers and small clusters have been observed by Tumminello et al [27] for agents in stock market data. Crossover to a dimerised state occurs as γ is increased.…”
Section: Model Bsupporting
confidence: 87%
“…Some real data are available to this respect. It has been shown that within a small interval of time most clusters are of size 2 [26,27] which can be termed as 'dimerisation'. Another observation is regarding the activity, i.e., the distribution of the volume of individual trade that also follows a power law with an exponent ≃4.3 [28].…”
Section: Introductionmentioning
confidence: 99%
“…39 to investigate preferential credit links between banks and firms based on their mutual credit relationships or ( ii ) in Ref. 40 to identify clusters of investors from their real trading activity in a financial market. Further details about the methodology, specifically applied to mobile phone data, can also be found in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…we consider the investor not active on day t. According to Tumminello et al (2012), in the present study, we set θ = 0.01. Roughly speaking, investors in a buy (sell) state can be seen as acting as net buyers (sellers), while investors in a buy and sell state can be thought as intermediaries or day traders.…”
Section: Definition Of the Variablesmentioning
confidence: 99%